PEG-400 as a carbon synthon: highly selective synthesis of quinolines and methylquinolines under metal-free conditions. Issue 15 (2nd July 2021) - Ding, Chengcheng; Li, Shichen; Feng, Kaili; Ma, Chen
Abstract : The remarkable feature of this work was using green, non-toxic PEG-400 as a carbon synthon for highly selective synthesis of quinolines (quinoxalines) and methylquinolines (methylquinoxalines) under metal-free conditions. Abstract : A metal-free, peroxide-free, and efficient procedure for the highly selective synthesis of quinolines and methylquinolines was reported. The main feature of this method was that the same substrate can produce quinolines and methylquinolines, respectively, under different reaction conditions. PEG-400 was used as both a reactant and solvent in this reaction. The utility of the designed procedure was also demonstrated by the derivatization of the products to bioactive compounds.